Decolonizing curatorial ways: Curating from Sámi perspective (PlaySpace, 2023)
The paper explores multiple perspectives on curating indigenous art and builds upon the case project of the nongraduate program for Sámicurators and its part realized in autumn 2022 at the SámiCenter for Contemporary Art in Karasjok. The curatorial ways are discussed from a threefold perspective: decolonizing curatorial practice, nonhierarchy of narratives, and pluriversal curating. The findings outline the main tools applied, such as the involvement of Sámicurators and scholars, nonindigenous scholars working with Indigenous art, the use of the lecture, presentation, and experience formats, and language use. The value of the project was in the unfolding of a broad perspective of what curating Indigenous art and research can be.